Phenotypic and Genotypic Identification of Acinetobacter baumannii with their Antibiotic Sensitivity Pattern Isolated from Different Specimens at a Tertiary Care Hospital in Dhaka City of Bangladesh - Sharmin, Rizwana; Shamsuzzaman, SM; Hossain, Md Faruk; Uddin, Muhammed Imran; Sultana, Farmin; Rahman, Sanzida (Bangladesh Journal of Medical Microbiology, 2025)
Background: Acinetobacter baumannii is an important opportunistic pathogen that causes serious nosocomial infections. Its ability to adhere to surfaces, forming biofilms, acquiring genetic materials from unrelated genera is making it a dangerous organism causing high morbidity and mortality. Objective: The goal of this study was to isolate and identify Acinetobacter baumannii from various samples and to identify the pattern of antibiotic resistance. Methodology: This cross-sectional study was conducted in the Department of Microbiology of Dhaka Medical College, Dhaka, Bangladesh over the course of January 2022 to December 2022. Collected samples were processed and inoculated in media, incubated aerobic at 370 C for 24 hours. Phenotypic identification of Acinetobacter species was done by observing colony morphology on media and growth at 420 C on agar was also done. Genotypic identification of Acinetobacter baumannii was done by blaOXA-51 like gene by PCR. The antimicrobial susceptibility test of all Acinetobacter baumannii isolates was determined by modified Kirby-Bauer disc diffusion technique using Mueller-Hinton agar plates. Results: Out of 275 culture positive clinical samples 14.2% isolates were Acinetobacter baumannii. Among the 39 Acinetobacter baumannii isolates 53.9% were multidrug-resistant, 33.3% were extended drug-resistant and 12.8% were pan drug-resistant. The highest (89.7%) number of Acinetobacter baumannii showed resistance to amoxiclav, ceftazidime and ciprofloxacin and least to colistin (30.8%). Conclusion: In conclusion Acinetobacter baumannii has been isolated frequently form the clinical specimens, and mostly are multi-drug resistant. Bangladesh Journal of Medical Microbiology, July 2024;18(2):109-113